The future of the world's climate - Henderson-Sellers, A. (World survey of climatology., 2012)
"The study of climate today seems to be dominated by global warming, but these predictions of climatic models must be placed in their geological, paleo-climatic, and astronomical context to create a complete picture of the Earth's future climate. The Future of the World's Climate presents that perspective with data and projections that have emerged from more technologically advanced and accurate climate modeling. The book is comprised of 18 new and revised chapters that feature reviews of current climate science. The authors are drawn from all over the world and from the highest regarded peer-reviewed groups. Each chapter has undergone major revisions and new content has been added throughout. Authored by the world's leading climate scientists, most of whom are also contributing authors to the IPCC Assessment Reports. More than 200 tables, diagrams, illustrations, and photographs Climate modeling technology is more advanced and precise than it was 15 years ago -- a major implication featured in this new edition"--Provided by publisher.